Experimental Investigation on SI Engine Emissions via EGR and catalytic converter with air injection mechanism / MVS Murali Krishna...[et al.] - MVS Murali, Krishna,; Kumar, S Narasimha; Kolli, Vamsi Krishna; Sreeram, Barathula (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Exhaust emissions emitted from spark ignition engines cause air pollution, human health hazards and ecological imbalance. Hence, effective curtail of these is an essential task. For this, an experimental evaluation was carried out on emissions and performance characteristics of the four-stroke three-cylinder Maruthi engine at varied brake power. Three different techniques, initially the exhaust gas recirculation (EGR) system was coupled to the test engine and varied from 0 to 10% for estimation of optimal value. Secondly, the provision of the catalytic converter with the copper as a catalyst and finally by the air injection mechanism of 60 l/m into the catalytic converter is executed and evaluated for optimum emission reduction. Also, the combined effect of these techniques on the characteristics was analysed. From the results, it was found that up to an EGR rate of 5%, an enhancement of 2% in brake thermal efficiency and a reduction of 9.5% in brake specific fuel consumption, 21% in carbon monoxide (CO), 19% in un-burnt hydrocarbon (UHC) and 29% in NOx emissions and a further increase in the EGR rate causes performance deterioration. The NOx emissions decreased by 44% at 7% of EGR. The catalytic converter setup alone decreased CO and UHC by 40% and by application of air injection it was 60%. The CO& UHC emissions decreased by 54% &52% respectively at 7% EGR rate combined with the catalytic converter and air injection mechanism.